Coated lithium supplement material, preparation method and application thereof, and lithium ion battery
By covering carbon-coated lithium iron phosphate on the surface of Li2NiO2 of the lithium supplement material, it forms a coated lithium supplement material, which solves the problems of poor stability and poor electrochemical performance of the existing lithium supplement material in the air, and achieves higher air stability and electrochemical performance.
Patent Information
- Application Number
- CN202411818692.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
The poor stability of existing lithium supplement materials in the air leads to poor electrochemical performance in applications and is prone to react with moisture and carbon dioxide to form residual alkali, reducing its specific capacity and the cycle life of the battery.
A clad lithium supplement material is used, which includes Li2NiO2 as a substrate, and a cladding layer is formed by covering carbon-coated lithium iron phosphate on its surface. The preparation method of the material includes mixing Li2NiO2, FePO4, lithium source and carbon source in the presence of a solvent to form a precursor solution, followed by drying and sintering to form a coated lithium supplement material.
The air stability of lithium supplement material is improved, the formation of residual alkali is avoided, its specific capacity is maintained, the electrochemical performance is enhanced, and the process is simple and easy to promote on a large scale.
Smart Images

Figure CN119812243A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a coated lithium supplement material, a preparation method and application thereof, and a lithium ion battery. Background Art
[0002] With the continuous development of lithium-ion battery technology, people require lithium-ion batteries to show higher energy density and longer cycle life than before. Improving the energy density and cycle life of lithium-ion batteries is crucial to achieving the global zero-carbon strategy. However, due to the formation and regeneration of SEI film during the initial formation and the cycle process, lithium-ion batteries inevitably lose active lithium, which significantly reduces the energy density and cycle life of lithium-ion batteries.
[0003] Lithium supplements can effectively replenish the loss of active lithium. Among them, Li2NiO2 (LNO) is a lithium supplement that is easy to scale up and has a capacity of about 300 mAh g -1 Irreversible capacity and 3.5V (vs.Li / Li + ) decomposition voltage, becoming one of the important additives to improve the energy density and cycle life of lithium-ion batteries.
[0004] However, LNO easily reacts with moisture and carbon dioxide in the air to form residual alkali substances such as LiOH and Li2CO3 on the surface. The residual alkali has low electronic conductivity, which increases the electrochemical polarization of LNO, reduces the capacity of LNO, and weakens its lithium replenishment effect. At the same time, the residual lithium on the surface is also an electrochemically inactive phase, further reducing the specific capacity of LNO. More importantly, the residual alkali on the surface will cause the positive electrode slurry to gel, which seriously hinders the production of batteries.
[0005] In recent years, researchers have modified the surface of LNO by surface coating. For example, phosphorus-containing compounds, carbon and metal carbides, polysiloxanes, zirconium dioxide and boron oxide, alkyl phosphates, carbon and metal borides, Li2Se, carbon and metal oxides, oxides or solid electrolytes, and Li3PO4 have been used to coat LNO to improve its air stability. However, most of these modified substances are electrochemically inactive substances, which will sacrifice the specific capacity of the lithium supplement. Although Li2Se is electrochemically active, it is also easy to react with moisture in the air to generate LiHSe and LiOH, which is not conducive to protecting the surface of LNO.
[0006] Therefore, how to improve the air stability of LNO through a simple and appropriate method without sacrificing its specific capacity too much is crucial for the further promotion and application of LNO.
[0007] CN116387475A discloses a method for preparing a positive electrode material with a lithium supplement function, which is characterized by comprising: mixing a lithium iron phosphate precursor and a lithium supplement material to obtain a first mixture; adding a dispersant to the first mixture and then ball milling to obtain a second mixture; grinding and mixing the second mixture with a lithium source and a carbon source to obtain a third mixture; sintering the third mixture to prepare a positive electrode material. Although the solution coats the carbon and the lithium supplement agent on the surface of the lithium iron phosphate, the lithium supplement agent as a coating layer material is still easily corroded by moisture and carbon dioxide in the air.
[0008] CN115353085A discloses a method for preparing a lithium iron phosphate composite material containing a lithium supplement, characterized in that it comprises the following steps: S1. mixing a lithium source, a phosphorus source, an iron source, a carbon source, a lithium supplement and a solvent to prepare a lithium iron phosphate slurry; the D50 of the lithium supplement is 0.10 μm-0.70 μm; the D50 of the solid particles in the lithium iron phosphate slurry is 0.45 μm-1.70 μm; S2. drying the lithium iron phosphate slurry to obtain a lithium iron phosphate containing a lithium supplement Lithium precursor; S3. Sintering the lithium iron phosphate precursor containing the lithium supplement agent to obtain a lithium iron phosphate composite material precursor, wherein the sintering temperature is 500°C-800°C; Although this solution evenly disperses the lithium supplement agent in the lithium iron phosphate, the lithium supplement agents mentioned therein, such as Li2O, Li2NiO2, Li5FeO4, and Li3P, are highly sensitive to moisture, and simple mixing with lithium iron phosphate still cannot ensure their air stability, and they are very likely to fail in actual production applications and cannot exert their lithium supplement capacity. Summary of the invention
[0009] The purpose of the present invention is to solve the problems of poor air stability of lithium supplement agents in the prior art and poor electrochemical performance after being applied to batteries.
[0010] In order to achieve the above-mentioned object, the first aspect of the present invention provides a coated lithium supplement material, which comprises a substrate and a coating layer coated on the surface of the substrate; the substrate comprises Li2NiO2; the coating layer comprises carbon-coated lithium iron phosphate;
[0011] The mass ratio of the Li2NiO2 to the lithium iron phosphate is 1:0.03-0.15;
[0012] The mass of the carbon element in the coating layer accounts for 0.03-0.375wt% of the total mass of the coated lithium supplement material;
[0013] The average particle diameter of the coated lithium supplement material is 13-18 μm.
[0014] The second aspect of the present invention provides a method for preparing the coated lithium supplement material according to the first aspect, the method comprising:
[0015] (1) In the presence of a solvent, Li2NiO2, FePO4, a lithium source and a carbon source are mixed to obtain a precursor solution;
[0016] (2) drying the precursor solution to obtain a precursor powder;
[0017] (3) In the presence of an inert gas, the precursor powder is subjected to a first sintering and a second sintering in sequence to obtain the coated lithium supplement material; the temperature of the second sintering is 150-450° C. higher than the temperature of the first sintering;
[0018] In step (1), the molar ratio of the FePO4, the lithium source and the carbon source, calculated as FePO4, lithium element and carbon element, is 1:1.0-1.1:0.4-0.6;
[0019] The mass ratio of the Li2NiO2 and the FePO4 is 6-35:1.
[0020] The third aspect of the present invention provides a coated lithium supplement material prepared by the method described in the second aspect.
[0021] The fourth aspect of the present invention provides the application of the coated lithium supplement material described in the first aspect and the third aspect in the field of lithium ion battery technology.
[0022] The fifth aspect of the present invention provides a lithium ion battery, which includes: a positive electrode, a separator, and a negative electrode; the positive electrode is coated with a lithium supplement material; the lithium supplement material is the coated lithium supplement material described in the first aspect and the second aspect.
[0023] Compared with the prior art, the coated lithium supplement material provided by the present invention has the following beneficial effects:
[0024] (1) The preparation process is simple, highly reproducible, and easy to promote on a large scale;
[0025] (2) The coated lithium supplement material provided by the present invention has better air stability;
[0026] (3) The lithium supplement material provided by the present invention will not cause a significant attenuation of its specific capacity, which is conducive to ensuring its lithium supplement capacity;
[0027] (4) The coated lithium supplement material provided by the present invention has high compatibility with the positive electrode slurry and can be directly added to the positive electrode slurry without causing the slurry to gel, which is conducive to its large-scale use. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the coated lithium supplement material obtained in Example 1 provided by the present invention;
[0029] Figure 2 1 is a first cycle charge and discharge curve diagram of the materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 provided by the present invention;
[0030] Figure 3 1 is an air stability test chart of the materials obtained in Example 1 and Comparative Example 1 provided by the present invention;
[0031] Figure 4 It is a test spectrum result diagram of the 2p orbit of Fe of XPS of the materials obtained in Example 3 and Comparative Example 1 provided by the exemplary embodiment of the present invention. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] As mentioned above, the first aspect of the present invention provides a coated lithium supplement material, which includes a substrate and a coating layer coated on the surface of the substrate; the substrate includes Li2NiO2; the coating layer includes carbon-coated lithium iron phosphate;
[0034] The mass ratio of the Li2NiO2 to the lithium iron phosphate is 1:0.03-0.15;
[0035] The mass of the carbon element in the coating layer accounts for 0.03-0.375wt% of the total mass of the coated lithium supplement material;
[0036] The average particle diameter of the coated lithium supplement material is 13-18 μm.
[0037] Preferably, the average particle diameter of the coated lithium supplement material is 13.5-15.5 μm.
[0038] Preferably, the mass ratio of the content of Li2NiO2 to the content of the lithium iron phosphate is 1: 0.05-0.15. The inventors found that under this preferred embodiment, the coated lithium supplement material obtained by the present invention has better electrochemical performance after being applied to the battery.
[0039] In order to better utilize the capacity of lithium iron phosphate, preferably, the mass of the carbon element in the coating layer accounts for 0.05-0.375wt% of the total mass of the coated lithium supplement material.
[0040] As mentioned above, the second aspect of the present invention provides a method for preparing the coated lithium supplement material according to the first aspect, the method comprising:
[0041] (1) In the presence of a solvent, Li2NiO2, FePO4, a lithium source and a carbon source are mixed to obtain a precursor solution;
[0042] (2) drying the precursor solution to obtain a precursor powder;
[0043] (3) In the presence of an inert gas, the precursor powder is subjected to a first sintering and a second sintering in sequence to obtain the coated lithium supplement material; the temperature of the second sintering is 150-450° C. higher than the temperature of the first sintering;
[0044] In step (1), the molar ratio of the FePO4, the lithium source and the carbon source, calculated as FePO4, lithium element and carbon element, is 1:1.0-1.1:0.4-0.6;
[0045] The mass ratio of the Li2NiO2 and the FePO4 is 6-35:1.
[0046] Preferably, in step (1), the solvent is water.
[0047] Preferably, in step (1), the molar ratio of FePO4, lithium source and carbon source is 1:1.0-1.02:0.4-0.5, respectively, in terms of FePO4, lithium element and carbon element. The inventors found that under this preferred embodiment, the lithium supplement material obtained by the present invention has better air stability and better electrochemical performance after being applied to batteries.
[0048] Preferably, the mass ratio of the Li2NiO2 to the FePO4 is 6-22: 1. The present invention has found through creative research that excessive Li2NiO2 will lead to incomplete coating of lithium iron phosphate, while excessive FePO4 will lead to excessive lithium iron phosphate being formed in the form of isolated islands and failing to be coated on Li2NiO2; therefore, the present invention preferably limits the mass ratio of Li2NiO2 to FePO4 to 6-22: 1.
[0049] Preferably, the D50 of the Li2NiO2 is 11.5-15.5 μm.
[0050] More preferably, the D50 of the Li2NiO2 is 13.5-15.5 μm.
[0051] Preferably, the D50 of the FePO4 is 0.8-1.2 μm.
[0052] More preferably, the D50 of the FePO4 is 0.8-1.0 μm.
[0053] Through creative research, the present invention finds that controlling the D50 of Li2NiO2 and the D50 of FePO4 within the above-mentioned preferred range can form an optimal particle size difference between Li2NiO2 and FePO4, which is conducive to uniform coating, so that the obtained coated lithium supplement material has better air stability and better electrochemical performance after being applied to batteries.
[0054] It should be noted that D50 in the present invention refers to the particle size corresponding to when the cumulative particle size distribution percentage of the particles reaches 50%.
[0055] Preferably, in step (1), the lithium source is selected from at least one of lithium hydroxide, lithium acetate and lithium carbonate; more preferably lithium hydroxide and / or lithium acetate.
[0056] Preferably, in step (1), the carbon source is selected from at least one of glucose, sucrose, fructose, phenolic resin, and polyvinyl alcohol; more preferably, it is at least one of glucose, sucrose, and fructose.
[0057] Preferably, in step (1), the lithium ion concentration in the precursor solution is 0.02-0.08 mol / L.
[0058] More preferably, the lithium ion concentration in the precursor solution is 0.03-0.06 mol / L. The lithium ion concentration determines the solid content of the precursor solution. The present invention has found through creative research that too low a lithium ion concentration will lead to high water content, low evaporation efficiency, lengthy process, and greatly reduced energy consumption, while too high a concentration will lead to high viscosity of the precursor solution, severe agglomeration of particles after drying, which is not conducive to the uniform coating of Li2NiO2 by lithium iron phosphate. Therefore, the present invention preferably limits the lithium ion concentration in the precursor solution to 0.03-0.06 mol / L.
[0059] Preferably, in step (1), the mixing conditions include: time of 30-120 min, temperature of 25-60°C.
[0060] More preferably, the mixing is carried out under stirring conditions. The present invention has no particular requirement on the stirring speed, and the mixing can be carried out in a conventional manner in the art. For example, the stirring speed can be 1000-2000 rpm.
[0061] Further preferably, in order to obtain a uniformly coated coated lithium supplement material of the present invention, ultrasonic treatment is further performed before the mixing, and the ultrasonic conditions include: temperature of 25-60° C., time of 5-15 min, and frequency of 45-55 kHz.
[0062] Preferably, in step (2), the drying is carried out by spray drying, and the conditions of the spray drying include: a feed rate of 100-1500 mL / h; and an inlet air temperature of 120-300°C.
[0063] More preferably, the conditions for spray drying include: a feed rate of 400-1000mL / h; an inlet air temperature of 200-300°C. An appropriate feed rate helps to increase production and control particle size. A feed rate that is too low can easily lead to the separation of Li2NiO2 and FePO4 particles, making it difficult to form a uniform coating; if the feed rate is too fast, the atomized liquid will form excessive agglomeration, greatly increasing the particle size of the final product, which is not conducive to the electrochemical performance after its application in the battery; an appropriate inlet air temperature also plays a role in regulating the particle size. Too low an inlet air temperature causes the liquid to evaporate slowly and the particles to agglomerate in large quantities. Therefore, the present invention preferably limits the feed rate to 400-1000mL / h; and the inlet air temperature to 200-300°C.
[0064] Preferably, in step (3), the first sintering temperature is 300-400°C and the time is 1-5h; the second sintering temperature is 550-750°C and the time is 5-20h. The inventors found that under this preferred embodiment, the carbon source in the present invention can be cracked into amorphous carbon to obtain more ordered micro-regions, which is beneficial to the improvement of electrical conductivity, and can also prevent the excessive growth of lithium iron phosphate grains and Li2NiO2 particles. Excessively large particles will lead to poor electrochemical performance.
[0065] Preferably, the inert gas is selected from at least one of nitrogen and argon.
[0066] Preferably, the first sintering and the second sintering are each independently performed in a tube furnace.
[0067] As mentioned above, the third aspect of the present invention provides a coated lithium supplement material prepared by the method described in the second aspect.
[0068] As mentioned above, the fourth aspect of the present invention provides the use of the coated lithium supplement material described in the first aspect and the third aspect in the field of lithium ion battery technology.
[0069] As mentioned above, the fifth aspect of the present invention provides a lithium-ion battery, which includes: a positive electrode, a separator, and a negative electrode; the positive electrode is coated with a lithium supplement material; the lithium supplement material is the coated lithium supplement material described in the first and third aspects above.
[0070] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0071] Example 1
[0072] This example is used to illustrate that the coated lithium supplement material provided by the present invention is prepared by the following steps:
[0073] The D50 of Li2NiO2 is 13.5μm;
[0074] The D50 of FePO4 is 0.8 μm;
[0075] (1) Li2NiO2, FePO4, glucose and 0.0102 mol of lithium acetate were dissolved in 340 mL of water, and then subjected to ultrasound (time: 15 min, frequency: 50 kHz, temperature: 25°C) and stirring (time: 30 min, temperature: 25°C, speed: 1000 rpm) to obtain a precursor solution;
[0076] The lithium ion concentration in the precursor solution is 0.03 mol / L;
[0077] The molar usage ratio of the FePO4, the lithium acetate and the glucose, calculated as FePO4, the lithium element and the carbon element, is 1:1.02:0.4;
[0078] The mass ratio of Li2NiO2 to FePO4 is 20.92:1;
[0079] (2) spray drying the precursor solution to obtain a precursor powder; the spray drying conditions are: a feed rate of 400 mL / h; an inlet air temperature of 250° C.;
[0080] (3) In the presence of nitrogen, the precursor powder is placed in a tube furnace and sequentially sintered for a first sintering and a second sintering to obtain the coated lithium supplement material S1; the first sintering temperature is 350° C. and the time is 3 h; the second sintering temperature is 700° C. and the time is 8 h.
[0081] Example 2
[0082] This example is used to illustrate that the coated lithium supplement material provided by the present invention is prepared by the following steps:
[0083] The D50 of Li2NiO2 is 14.5μm;
[0084] The D50 of FePO4 is 0.8 μm;
[0085] (1) Li2NiO2, FePO4, glucose and 0.01 mol of lithium acetate were dissolved in 200 mL of water, and then subjected to ultrasound (time: 10 min, frequency: 50 kHz, temperature: 25°C) and stirring (time: 60 min, temperature: 25°C, speed: 1000 rpm) to obtain a precursor solution;
[0086] The lithium ion concentration in the precursor solution is 0.05 mol / L;
[0087] The molar usage ratio of the FePO4, the lithium acetate and the glucose, calculated as FePO4, the lithium element and the carbon element, is 1:1:0.45;
[0088] The mass ratio of Li2NiO2 to FePO4 is 10.46:1;
[0089] (2) spray drying the precursor solution to obtain a precursor powder; the spray drying conditions are: a feed rate of 600 mL / h; an inlet air temperature of 250° C.;
[0090] (3) In the presence of nitrogen, the precursor powder is placed in a tube furnace and sequentially sintered for a first sintering and a second sintering to obtain a coated lithium supplement material S2; the first sintering temperature is 380°C and the time is 4 hours; the second sintering temperature is 650°C and the time is 7 hours.
[0091] Example 3
[0092] The D50 of Li2NiO2 is 15.5μm;
[0093] The D50 of FePO4 is 1 μm;
[0094] (1) Li2NiO2, FePO4, glucose and 0.0102 mol of lithium hydroxide were dissolved in 170 mL of water, and then subjected to ultrasound (time: 5 min, frequency: 50 kHz, temperature: 25°C) and stirring (time: 120 min, temperature: 25°C, speed: 1000 rpm) to obtain a precursor solution;
[0095] The lithium ion concentration in the precursor solution is 0.06 mol / L;
[0096] The molar usage ratio of the FePO4, the lithium acetate and the glucose, calculated as FePO4, the lithium element and the carbon element, is 1:1.02:0.5;
[0097] The mass ratio of Li2NiO2 to FePO4 is 6.9735:1;
[0098] (2) spray drying the precursor solution to obtain a precursor powder; the spray drying conditions are: a feed rate of 1000 mL / h; an inlet air temperature of 200° C.;
[0099] (3) In the presence of nitrogen, the precursor powder is placed in a tube furnace and sequentially sintered for a first sintering and a second sintering to obtain a coated lithium supplement material S3; the first sintering temperature is 400° C. and the time is 3 h; the second sintering temperature is 700° C. and the time is 5 h.
[0100] Example 4
[0101] This example is carried out in a similar manner to Example 1, except that, in this example, the amount of lithium acetate is kept unchanged, but the molar ratio of FePO4, lithium acetate and glucose in terms of FePO4, lithium element and carbon element, respectively, is 1:1:0.6.
[0102] The rest are the same as in Example 1.
[0103] The coated lithium supplement material S4 is prepared.
[0104] Example 5
[0105] This embodiment is carried out in a similar manner to Embodiment 1, except that, in this embodiment, the amount of FePO4 is controlled to remain unchanged, but the mass ratio of Li2NiO2 to FePO4 is 34.87:1.
[0106] The rest are the same as in Example 1.
[0107] The coated lithium supplement material S5 was prepared.
[0108] Example 6
[0109] This embodiment is carried out in a similar manner to that of Embodiment 1, except that in this embodiment, the D50 of Li2NiO2 is 11.5 μm.
[0110] The rest are the same as in Example 1.
[0111] The coated lithium supplement material S6 was prepared.
[0112] Example 7
[0113] This example is carried out in a manner similar to that of Example 1, except that, in this example, the amount of lithium acetate is kept unchanged, but the lithium ion concentration in the precursor solution is 0.08 mol / L (that is, Li2NiO2, FePO4, glucose and 0.0102 mol of lithium acetate are dissolved in 127.5 mL of water).
[0114] The rest are the same as in Example 1.
[0115] The coated lithium supplement material S7 was prepared.
[0116] Example 8
[0117] This embodiment is carried out in a similar manner to that of Embodiment 1, except that, in this embodiment, the first sintering temperature is 700° C. and the time is 3 h; the second sintering temperature is 700° C. and the time is 8 h.
[0118] The rest are the same as in Example 1.
[0119] The coated lithium supplement material S8 was prepared.
[0120] Example 9
[0121] This example is carried out in a similar manner to Example 1, except that in this example, the spray drying conditions are: a feed rate of 1500 mL / h; and an inlet air temperature of 250°C.
[0122] The rest are the same as in Example 1.
[0123] The coated lithium supplement material S9 was prepared.
[0124] Comparative Example 1
[0125] This comparative example uses Li2NiO2 (D50 is 13.5 μm) as a comparison.
[0126] Comparative Example 2
[0127] The D50 of Li2NiO2 is 17μm;
[0128] The D50 of FePO4 is 1.5 μm;
[0129] (1) Li2NiO2, FePO4, glucose and 0.0102 mol of lithium acetate were dissolved in 102 mL of water, and then subjected to ultrasound (time: 5 min, frequency: 50 kHz, temperature: 25°C) and stirring (time: 15 min, temperature: 25°C, speed: 1000 rpm) to obtain a precursor solution;
[0130] The lithium ion concentration in the precursor solution is 0.1 mol / L;
[0131] The molar usage ratio of the FePO4, the lithium acetate and the glucose, calculated as FePO4, the lithium element and the carbon element, is 1:1.02:0.5;
[0132] The mass ratio of Li2NiO2 to FePO4 is 10.46:1;
[0133] (2) spray drying the precursor solution to obtain a precursor powder; the spray drying conditions are: a feed rate of 2000 mL / h; an inlet air temperature of 300° C.;
[0134] (3) In the presence of nitrogen, the precursor powder is placed in a tubular furnace and sequentially subjected to a first sintering and a second sintering to obtain material DS2; the first sintering is performed at a temperature of 450°C for 3 hours; the second sintering is performed at a temperature of 700°C for 8 hours.
[0135] Comparative Example 3
[0136] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, the amount of lithium acetate is controlled unchanged, but the molar ratio of FePO4, lithium acetate and glucose calculated as FePO4, lithium element and carbon element respectively is 1:1.02:1.5.
[0137] The rest are the same as in Example 1.
[0138] Material DS3 was prepared.
[0139] Comparative Example 4
[0140] This comparative example is carried out using a process similar to that of Example 1, except that the amount of FePO4 in this comparative example is controlled to remain unchanged, but the mass ratio of Li2NiO2 to FePO4 is 52.3:1.
[0141] The rest are the same as in Example 1.
[0142] Material DS4 was prepared.
[0143] The parameter characteristics of the materials prepared in the above examples are shown in Table 1.
[0144] Table 1
[0145]
[0146] The present invention also exemplarily provides a SEM image of the coated lithium supplement material obtained in Example 1 ( Figure 1 ), it can be seen from the figure that the surface of the coated lithium supplement material is obviously coated with a layer of small particles, indicating the successful coating of lithium iron phosphate.
[0147] Test Example 1
[0148] 0.08 g of the material provided in the above example was mixed with 0.01 g of acetylene black, 0.01 g of polyvinylidene fluoride and 0.5 mL of N-methylpyrrolidone to obtain a slurry, which was coated on an aluminum foil to prepare a positive electrode sheet. The positive electrode sheet, a metal lithium sheet (negative electrode), a separator and an electrolyte were assembled into a CR2032 button battery.
[0149] The assembled battery was tested for its charge capacity in grams at a voltage range of 2.0-4.4V and a charge rate of 0.1C. The test results are shown in Table 2.
[0150] Table 2
[0151] <![CDATA[Charge specific capacity (mAhg -1 )]]> Example 1 393.6 Example 2 391.5 Example 3 389.1 Example 4 388.8 Example 5 387.1 Example 6 389 Example 7 385.2 Example 8 384.9 Example 9 385.7 Comparative Example 1 384.3 Comparative Example 2 248 Comparative Example 3 350.2 Comparative Example 4 378.2
[0152] It can be seen from Table 2 that the coated lithium supplement material provided by the present invention has better electrochemical performance after being applied to the battery; when there is no lithium iron phosphate coating, the capacity of Li2NiO2 is affected by the residual alkali on the surface, and the capacity is only 384.3 mAh g -1 If the particle size of Li2NiO2 and FePO4 is too large and the feeding speed is too fast, the specific capacity of the material will drop significantly, only 248 mAh g -1 When the carbon content is too high, although the conductivity and air stability can be improved, the content of active substances is greatly reduced, resulting in a material specific capacity of only 350.2 mAh g -1 In addition, when only 2% of lithium iron phosphate was coated, the specific capacity was still slightly reduced to 378.2 mAh g due to incomplete coating. -1 .
[0153] The present invention also provides, by way of example, the first cycle charge and discharge curves of the materials obtained in Comparative Example 1, Example 1 and Comparative Example 2 ( Figure 2 ). It can be seen from the figure that the material obtained in Comparative Example 1 has a voltage platform at 3.5V during charging, corresponding to the delithiation of Li2NiO2. In the charge-discharge curve of the material obtained in Example 1, additional charge-discharge platforms are observed at 3.46 and 3.37V, corresponding to the delithiation voltage of lithium iron phosphate, indicating that lithium iron phosphate is successfully coated on the surface of Li2NiO2. Comparative Example 2 also observed the charge-discharge platform characteristics of Li2NiO2 and lithium iron phosphate, but due to its large particle size, the lithium replenishment capacity is not well utilized.
[0154] Test Example 2
[0155] This test example is used to illustrate the air stability of the coated lithium supplement material obtained by the present invention;
[0156] Test method: Place the sample to be tested in an environment with a relative humidity of 40% and a temperature of 25°C for 2 days and then place it in a Raman spectrometer for testing.
[0157] Test results see Figure 3
[0158] from Figure 3 As can be seen from (a), the main peak of Comparative Example 1 did not change after exposure for 0 days and 2 days, indicating that its main structure did not change. Figure 3 After the partial area of (a) is enlarged, it can be found that after the comparative example 1 is exposed to the ambient atmosphere for 2 days, the -1 and 3600cm -1 There are obvious characteristic peaks of Li2CO3 and LiOH on the left and right ( Figure 3 (bc)), indicating that the surface structure of the sample in comparative example 1 has changed and residual alkali has been generated. In Example 1, the Raman spectra of the samples that were not exposed and exposed for 2 days both observed obvious D-band and G-band characteristic peaks, indicating the presence of carbon on the surface. Figure 3 (d) Local magnification Figure 3 (e) and 1(f), it can be seen at 950cm -1 There is an obvious characteristic peak, corresponding to PO4 of lithium iron phosphate 3- Therefore, the above results prove that carbon-coated lithium iron phosphate successfully forms a coating on the surface of Li2NiO2. By comparing the characteristic peak positions of Li2CO3 and LiOH, it is found that no obvious peak appears. Therefore, Figure 3 It was demonstrated that carbon-coated lithium iron phosphate was successfully coated on the surface of Li2NiO2 and effectively inhibited the formation of residual alkali.
[0159] The present invention also provides exemplary XPS test spectrum results of the Fe 2p orbital of the materials obtained in Example 3 and Comparative Example 1 ( Figure 4 ). Since XPS analyzes the surface signal of the material, it can be used to identify the coating layer. It can be seen from the figure that Comparative Example 1 has no obvious characteristic peaks, indicating that there is no Fe-related substance on its surface, while Example 3 shows a pair of obvious peaks at 710 and 725 eV, indicating that the surface contains Fe elements, indicating the successful coating of lithium iron phosphate.
[0160] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A coated lithium supplement material, characterized in that: The material comprises a substrate and a coating layer coated on the surface of the substrate; the substrate comprises Li2NiO2; the coating layer comprises carbon-coated lithium iron phosphate; The mass ratio of the Li2NiO2 to the lithium iron phosphate is 1:0.03-0.15; The mass of the carbon element in the coating layer accounts for 0.03-0.375wt% of the total mass of the coated lithium supplement material; The average particle diameter of the coated lithium supplement material is 13-18 μm.
2. The coated lithium supplement material according to claim 1, characterized in that: The average particle diameter of the coated lithium supplement material is 13.5-15.5 μm; And / or, the mass ratio of the content of Li2NiO2 to the lithium iron phosphate is 1:0.05-0.15; And / or, the mass of the carbon element in the coating layer accounts for 0.05-0.375wt% of the total mass of the coated lithium supplement material.
3. A method for preparing the coated lithium supplement material according to claim 1 or 2, characterized in that: The method includes: (1) In the presence of a solvent, Li2NiO2, FePO4, a lithium source and a carbon source are mixed to obtain a precursor solution; (2) drying the precursor solution to obtain a precursor powder; (3) In the presence of an inert gas, the precursor powder is subjected to a first sintering and a second sintering in sequence to obtain the coated lithium supplement material; the temperature of the second sintering is 150-450° C. higher than the temperature of the first sintering; In step (1), the molar ratio of the FePO4, the lithium source and the carbon source, calculated as FePO4, lithium element and carbon element, is 1:1.0-1.1:0.4-0.6; The mass ratio of the Li2NiO2 and the FePO4 is 6-35:
1.
4. The method according to claim 3, characterized in that In step (1), the molar ratio of the FePO4, the lithium source and the carbon source, calculated as FePO4, lithium element and carbon element, is 1:1.0-1.02:0.4-0.5 respectively; And / or, the mass ratio of the Li2NiO2 and the FePO4 is 6-22:
1.
5. The method according to any one of claims 3 or 4, characterized in that The D50 of the Li2NiO2 is 11.5-15.5 μm; Preferably, the D50 of the Li2NiO2 is 13.5-15.5 μm; And / or, the D50 of the FePO4 is 0.8-1.2 μm; Preferably, the D50 of the FePO4 is 0.8-1.0 μm.
6. The method according to any one of claims 3 to 5, characterized in that: In step (1), the lithium ion concentration in the precursor solution is 0.02-0.08 mol / L; Preferably, the lithium ion concentration in the precursor solution is 0.03-0.06 mol / L.
7. The method according to any one of claims 3 to 6, characterized in that: In step (1), the mixing conditions include: time of 30-120 min, temperature of 25-60° C.; And / or, in step (2), the drying is carried out by spray drying, and the conditions of the spray drying include: a feed rate of 100-1500 mL / h; an inlet air temperature of 120-300° C.; And / or, in step (3), the first sintering temperature is 300-400°C, and the time is 1-5 hours; the second sintering temperature is 550-750°C, and the time is 5-20 hours.
8. The coated lithium supplement material prepared by the method according to claims 3-7.
9. Application of the coated lithium supplement material according to claims 1, 2 and 8 in the field of lithium ion battery technology.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises: a positive electrode sheet, a separator, and a negative electrode sheet; the positive electrode sheet is coated with a lithium supplement material; the lithium supplement material is the coated lithium supplement material according to claims 1, 2, and 8.
Citation Information
Patent Citations
Positive plate, lithium-ion battery positive lithium-supplementing material and preparation method of material
CN109786746A
Lithium iron phosphate composite material, preparation method and application
CN114242980A
Modified positive electrode lithium supplement additive and preparation method and application thereof
CN115832471A
Lithium-supplementing positive electrode material as well as preparation method and application thereof
CN119050509A